Volatile and semivolatile organic compound emissions from polymers used in commercial products during thermal degradation. Issue 3 (March 2020) - Noguchi, Miyuki; Yamasaki, Akihiro
Abstract: Emissions of volatile and semivolatile organic compounds from various kinds of polymer sheets during thermal degradation process were determined by the passive flux sampling method. The polymer sheets used were commercial products made of: polyethylene (PE), ethylene-vinyl acetate (EVA), polypropylene (PP), polyacetal (POM), polycarbonate (PC)), and polymer sheet samples: poly (methyl methacrylate) (PMMA), polyethylene terephthalate (PET), polystyrene (PS) and four types of poly vinyl chloride (PVC) with different contents of additives; (bis(2-ethylhexyl)phthalate (DEHP)), and triphenylphosphine (TPP)). The emission fluxes from the polymer sheets were measured for up to 30 days stored under a constant temperature (25–75 °C). Emission of various kinds of chemicals were observed from PVC sheets including and products of polymer degradation, while emission of hydrocarbons were dominant from PE, PP and EVA, and the emission of an additive (DEP) only was observed from PMMA, PET, POM and PC. The TVOC (total VOC) emission rates from PVC sheets with DEHP and TPP (soft PVCs) were in the range of 30–120 mg m −2 h−1 at 50 °C, which were much higher than the TVOC emission rates from other polymers. The emission rates for these chemicals for the same sampling period increased dramatically as the temperature increased. The temperature-dependences of the emission rates from the soft PVC sheet for a given sampling period could be expressed using an Arrhenius-type equation, and the apparent emission activation energy E A, correlated well with the enthalpy of vaporization ΔH VAP by the following empirical equation. E A = 2.27 Δ H vap − 115 We also found that the emission rates of chemicals changed with time with different changing characters, and the activation energy decreased with the progress of the polymer degradation. Abstract : Atmospheric chemistry; Air quality; Environmental analysis; Waste treatment; Environmental chemical engineering; Environmental hazard; Semivolatile organic compounds (SVOCs) volatile organic compounds (VOCs) polymeric materials emissions passive flux sampling.